Homecourt Application Through Zoom Media To Improve Student Dribbling Techniques In Handball Courses In Physical Education Study Program FKIP UNIB - Bogy Restu Ilahi; Defliyanto Defliyanto; Syafrial Syafrial (Universitas Bengkulu, 2021)
This research is a Classroom Action Research in the scope of education carried out by lecturers, researchers in their class or together with other people.Increasing basic dribbling technique skills from before using the homecourt application method through online-based zoom media and after using the homecourt application method through zoom-based media. online in the pre-cycle, it is proven that there has been no improvement because the homecourt application method has not been implemented. 40% of the 12 students who got complete scores with an average score of 67 out of 30 students. There was a significant increase in cycle II, there was an increase in dribbling skills in Handball games with the homecourt application method through online-based zoom media with 2 students who became guards. Evidenced by the results of research with an increase in completeness results to 19 students who completed with an average score in Handball learning of 72.25